Prevalence and associated risk factors of diabetic peripheral neuropathy among diabetic patients in National Center of Diabetes in Yemen - Al-Washali, Abeer Yahya Ahmed; Ariffin, Ahmad Azuhairi; Abdul Rahman, Hejar; Y. W., Amani (Community Health Society Malaysia, 2014)
Background: Diabetes mellitus is one of the important public health concerns challenging the world in the 21st century. Neuropathy is one of the most frequent complications of diabetes, and the most common type of neuropathy is the diabetic peripheral neuropathy. Diabetic peripheral neuropathy is common and frequent cause of morbidity and disability. In Yemen, the data on the prevalence and risk factors of diabetic peripheral neuropathy remains scarce. Aim: The purpose of this study is to determine the prevalence and associated risk factors of diabetic peripheral neuropathy in the National Centre of Diabetes in Yemen. Materials and Methods: A cross-sectional study of 306 diabetic patients was conducted in the National Centre of Diabetes in Yemen from February to May 2014. The diabetic peripheral neuropathy was assessed by using Neuropathy Symptoms Score and Neuropathy Disability Score. Result: The prevalence of diabetic peripheral neuropathy was 56.2%, and it increased with diabetes duration, HbA1c (from 34.6% in patients with HbA1c <7% to 61.3% in patients with HbA1c >9%) and with increased in total cholesterol (P = 0.0001 95%Cl 4.9 – 5.1). The diabetic peripheral neuropathy was less among obese patients (P = 0.03). There was no significant association between the diabetic peripheral neuropathy and diabetes type (P = 0.373) and hypertension (P = 0.08). Conclusion: The prevalence of diabetic peripheral neuropathy among diabetic patients in the National Centre of Diabetes in Yemen was 56.2%. Diabetes duration, HbA1c, body mass index and total cholesterol were the associated risk factors of diabetic peripheral neuropathy.